Obsessed - Patterson, James, 1947-; Born, James O. (Patterson, James, 1947- Detective Michael Bennett thriller, 2023)
When a killer becomes obsessed with his oldest daughter, Detective Michael Bennett will do anything to keep his family safe as he races against time to crack this superstitious killer's code.